UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DENGAN MENERAPKAN MODEL PEMBELAJARAN SAINTIFIK PADA SISWA KELAS X AK2 SMK NEGERI 1 MUARA BUNGO - TIURMA ROULI (LP3M STKIP Muhammadiyah Muara Bungo, 2020)
The background in this study is the lack of awareness of students in the learning process so that students still feel embarrassed and reluctant to ask what they do not understand, interactions and communication between students and students or between students and teachers have not been established because group discussions are rarely held. The purpose of this study was to improve mathematical problem solving skills by applying the scientific learning model of class X Accounting students. 2. This type of research is classroom action research. The research setting consists of 1) research location 2) research time 3) research subjects. This research was conducted in two cycles. Cycle I had two meetings and cycle II had one meeting. In pre-cycle the class average score was 60, cycle I increased to 75, and in cycle II increased to 80. As for classical learning completeness in pre-cycle conditions was 60%, in cycle I it increased to 75%, and in cycle II it became 80%. The minimum score in pre-cycle conditions is 45, in cycle I it is 60, and in cycle II it increases to 62.While the maximum score in pre-cycle conditions is 85, cycle I is 93, and in cycle II it increases to 100.